THE INFLUENCE OF MAJOR SPORTS COMPETITIONS ON INVOLVING PEOPLE INTO AN ACTIVE LIFESTYLE - SEREBRYAKOVA Ekaterina Gennadievna («PHYSICAL CULTURE: UPBRINGING, EDUCATION, TRAINING», 2025)
The article is devoted to the study of the inﬂuence of large-scale sports events on the process of forming a commitment to a healthy lifestyle. The signifcance of the successes of representatives of Uzbekistan in the sports sphere, which contribute to the strengthening of public interest in regular physical activity, is considered. The empirical base of the study is presented by the results of a sociological survey, confrming the increase in the level of motivation of young people for systematic physical education and sports. In addition, an analysis of government measures aimed at developing mass sports, improving sports infrastructure and creating favorable conditions for the active participation of broad sections of the population in sports and physical education activities was conducted. Particular attention is paid to the role of sports as an important tool for the educational process, activating social interactions and improving the health of the nation.